Dramska forma in etična razsežnost besedila Gostija Simone Semenič - Jerkovič, Lara (Amfiteater (Ljubljana), 2022)
In this paper, we will focus on one of the most active and successful artists in the contemporary Slovenian theatre, the dramatist Simona Semenič, and one of her most theoretically intriguing texts, the feast or the story of a savory corpse or how roman abramovič, the character janša, julia kristeva, age 24, simona semenič and the initials z. i. found themselves in a tiny cloud of tobacco smoke (2010). We will look at how the text affects the viewer/reader, whom the author directly and constantly addresses through the character of the narrator. Based on an analysis of the form and content of the selected text, we will assess to what extent it can be classified as no-longer-dramatic text (Poschmann) or as “dramatic drama” ( dramatisches Drama – Birgit Haas) and put in the field of postdramatic theatre (Lehmann). The paper aims to analyse the (no longer or again?) dramatic form of the feast, the specifics of the author’s writing style and the construction of the text. On the other hand, it also aims to explain the author’s methods of emphasising the ethical and moral responsibility of those involved (especially the readers/ viewers) in the happening.
Keywords: drama; dramatic; dramatic form; dramatično; dramska forma; ethics; etika; Gostija; ne več dramski gledališki tekst; no-longer-draamtic text; postdramatic theatre; postdramsko gledališče; Semenič, Simona; The feast